MAS TURNAROUND FROM RED TO BLACK - Zainal Abidin , Nor Hafizah; Mohd Alwi, Norhayati; Mokhtar, Norsyahida; Puat Nelson, Sherliza (IIUM Journal of Case Studies in Management, 2025)
Malaysia Airline has gone through the ups and downs throughout the half-century that made the company mature enough. Two major incidents in 2014 and the pandemic in 2019 were turbulences that forced the company to be creative and innovative in its pursuit of survival. This case study eventually explores the magical touch made by MAS leadership. It also demonstrates how the company sustained its businesses through rapid developments in a highly volatile, uncertain and dynamic environment. Another objective of the case is to assist students or readers in applying their understanding to develop a business turnaround strategy based on its internal and external agile environments.